Англи хэлний заах арга зүйн сургалтад “моос” буюу бүх нийтэд нээлттэй онлайн сургалтыг ашиглах нь - ”Shaping the way we teach, 2” сургалтын жишээн дээр: Using MOOC’s for english-teaching professionals and preprofessionals - case study of “Shaping the way we teach, 2" - N., Khosbayar (Mongolian Journal of Foreign Languages and Cultures, 2023)
Massive Open Online Courses are web-based courses which have a goal of following unlimited participation. Although it began in the 1980’s, it has become free for everyone in last couple of years. Today most major universities are offering courses and they are working as partners with Courseria, Edx or Udocity webs. These courses help EL teachers and students who want to improve their crafts and skills. However it has spread and developed, still there are some challenges for students who wants to accomplish the course.